A comparison between qualitative and quantitative histories: the example of the efficient market hypothesis. Issue 4 (2nd October 2018) - Jovanovic, Franck
ABSTRACT: This paper uses the example of the history of the efficient market hypothesis (EMH) and citation analysis in order to investigate some differences between qualitative history and a quantitative history. The history of the EMH provides a telling example of the way quantitative analyses can supply different perspectives on the qualitative history of this hypothesis or complement it. For instance, since the EMH was proposed, several criticisms emerged. In addition, the definition and the scope of this hypothesis have been modified several times. Although the qualitative history of the EMH refers to these criticisms and these alternative definitions and scopes, qualitative tools cannot provide a clear measure of the impact of these criticisms and these modifications among economists. By studying the dissemination of the EMH, its major criticisms, and the answers economists provided, citation analysis sheds a different light on the history of the EMH.